Local normative climate shaping agency and agricultural livelihoods in sub-Saharan Africa - Petesch, Patti; Bullock, Renee; Feldman, Shelley; Badstue, Lone B.; Rietveld, Anne M.; Bauchspies, Wenda; Kamanzi, Adelbertus; Tegbaru, Amare; Yila, Jummai Othniel (2018)
We introduce the concept of local normative climate to improve understanding of community- level social processes that shape women’s and men’s sense of agency and capacities for taking important decisions, including in their agricultural livelihoods. The idea of normative climate is informed by feminist literature that addresses concerns for the contextual, fluid, and relational properties of gender norms. We apply normative climate to a qualitative examination of men’s and women’s assessments of decade-long changes in their decision-making capacity in two village case studies as well as comparatively with 24 village cases from seven sub-Saharan African countries. The case studies reveal how a normative climate is shaped by contextual influences that give rise to social processes where, for instance, changes in decision-making and agricultural opportunities may be perceived as empowering by only men in one village, and only by women in the other village. Comparative findings highlight how perceptions of agency are rooted in fluid normative expectations that evolve differently for women and men as they move through their life cycle and as local institutions and opportunities change.